Barhouma, Issa. “A Dialogue of Civilizations or a Conflict? A Balanced View for Coexistence,” Year 12, Issues 46-47 (Fall 1428 AH/ 2007 CE), Pp. 163-187. - برهومة, عيسى (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2007)
Issa Barhouma’s article discusses the theories of Fukuyama and Huntington, and attempts to bring the two approaches closer together with what was presented by Malik bin Nabi regarding the problem of civilization. Barhouma applies a comparative analytical approach because of its importance in detecting many of the issues. His article defines the term “civilization” linguistically and in common usage, and then addresses Malik bin Nabi's approach to civilization, Fukuyama’s thesis “The End of History,” and Huntington’s thesis “The Clash of Civilizations.” It concludes with an analysis on whether it is a dialogue of cultures or a clash of civilizations, and asks “Who will prevail?” and whether Arabs and Muslims will be able to liberate themselves from the West and its domination?